Proteins and lipids of glycosomal membranes from Leishmania tarentolae and Trypanosoma brucei - Colasante, Claudia; Voncken, Frank; Manful, Theresa; Ruppert, Thomas; Tielens, Aloysius G M; van Hellemond, Jaap J; Clayton, Christine (F1000Research, 2013)
In kinetoplastid protists, several metabolic pathways, including glycolysis and purine salvage, are located in glycosomes, which are microbodies that are evolutionarily related to peroxisomes. With the exception of some potential transporters for fatty acids, and one member of the mitochondrial carrier protein family, proteins that transport metabolites across the glycosomal membrane have yet to be identified. We show here that the phosphatidylcholine species composition of - Trypanosoma brucei glycosomal membranes resembles that of other cellular membranes, which means that glycosomal membranes are expected to be impermeable to small hydrophilic molecules unless transport is facilitated by specialized membrane proteins. Further, we identified 464 proteins in a glycosomal membrane preparation from - Leishmania tarentolae. The proteins included approximately 40 glycosomal matrix proteins, and homologues of peroxisomal membrane proteins - PEX11, GIM5A and GIM5B; PXMP4, PEX2 and PEX16 - as well as the transporters GAT1 and GAT3. There were 27 other proteins that could not be unambiguously assigned to other compartments, and that had predicted trans-membrane domains. However, no clear candidates for transport of the major substrates and intermediates of energy metabolism were found. We suggest that, instead, these metabolites are transported via pores formed by the known glycosomal membrane proteins.
Gesehen am 30.04.2021